International Double Taxation Avoidance (Domestic Legal Regulations and Fiscal Conventions Concluded by Romania) - Cornelia LEFTER (Theoretical and Applied Economics, 2010)

(untitled)
The avoidance of double taxation has been firstly introduced in the Romanian legislation in 1973. Due to the permanent development of the economic, legal, social, etc. and global environment, Romania adapted accordingly her legal tax provisions in tax law area. One of the most relevant moments is the accession of Romanian into European Union. During pre- and after accession phase Romania has adopted the mandatory European fiscal legislation. Beeing member of EU, Romania has indirectly amended many of its double tax treaties sparing the long process of legislative amendments, including individual renegotiation and amendment with each of the contracting EU member states.